Characterization of Streptomyces ambofaciens S2 and elucidation of its anti-fungal compounds for biocontrol of chilli anthracnose - Lim, Jefferey Seng Heng (2013)
Red chilli is one of the most important diets for Malaysian. However chili plants are susceptible to attacks by few diseases such as anthracnose and Chili Mozaic Virus (CMV). Anthracnose is being considered as the major disease due to the ability of the fungi to attack both pre and post harvest chili fruits. With the high impact of anthracnose on chilli fruits the use of chemical pesticides has been frequent and uncontrolled. The high usage of chemical pesticides has caused damage not only to the environment but also human health. Biological control has been suggested as an alternative to counter the effect of chemical pesticides. Actinomycetes especially those from the genus of streptomycetes have been well known as a potential biological control agent for most of the plant pathogens. This study was conducted with the aim to investigate the characteristics of Streptomyces ambofacines S2 and to isolate antifungal compounds produced towards anthracnose for use as a biopesticide. Colletotrichum capsici and Colletotrichum gleosporioides were isolated form infected chilli fruits using surface sterilization method. The fungi were later identified by targeting its internal transcribed spacer region (ITS). Molecular method confirmed that both C.capsici and C. gleosporioides were isolated. A total of 513 isolates of actinomycetes were isolated from 5 different soil samples from both Peninsular Malaysia and Sabah and Sarawak using soil dilution method. The antifungal activity was detected using disc diffusion method. Through disc diffusion testing, 6 potential isolates of Streptomyces spp. were chosen for further studies (morphology study, molecular identification and carbon sources utilization analysis). However, only Streptomyces ambofaciens S2 was chosen for cultural condition optimization and bioactive compound isolation due to the highest inhibition zone exhibited towards C. capsici (15 mm) and C. gleosporioides (16 mm). Metabolomic study conducted showed that Streptomyces spp. with antifungal producing abilities tend to produce more valine, isoleucine, leucine, asparagines, succinic acid and fructose, while non antifungal producing Streptomyces spp. produces more fatty acid,lactic acid, β glucose and gallic acid. Differences in the metabolite constituents have enable the used of metabolomic to characterize antifungal producing Streptomyces spp.from non antifungal producing Streptomyces spp. The impact of media composition and cultural conditions were conducted for S.ambofaciens S2 using shake flask fermentation. It was observed that S. ambofaciens S2 produced the highest antifungal compound when chitin and peptone were used as the carbon and nitrogen sources respectively, 0.2% NaCl, 3 days incubation time, 6 days seed age and initial pH 8 for the broth. An increased of 33% in the inhibition zone was noted when S. ambofaciens S2 was grown using this condition. Chitinase activity was observed to be the highest when the culture was incubated for 7 days with the activity of 0.192 U/ml. Specific activity at day 7 was recorded as 1.28 U/mg. Formulation of an oil based liquid biopesticide using 20% glycerol added to the Chitin Peptone Media showed that S.ambofaciens S2 extract was able to give an effectiveness of 80% when tested in vivo for controlling chilli anthracnose. Isolation of the bioactive compounds, indicated that the active compounds were eluted when 1:1 (hexane : ethyl acetate) was used. This active fraction was then subjected to purification using high pressure liquid chromatography (HPLC). The compound was white in colour when it was dried. Under liquid chromatography mass spectrocopy (LCMS) analysis, the compound was observed with the mass of 777.11 m/z. The compound was categorized under the group of polyenes. Results from this study demonstrated Streptomyces ambofaciens S2 could be used as an alternative pesticide for controlling anthracnose in chilli fruits. In addition, metabolomic method could be used as a new way of fast characterization of different species of streptomycetes.